Noise experiments in BRAHMMA subcritical system using isotopic Poisson source and accelerator based neutron source. Issue 1 (1st August 2022) - Ray, N K; Kumar, R; Patel, T; Sarkar, P S; Pant, L M
Abstract: Reactivity measurement using noise methods have been carried out in zero power subcritical system BRAHMMA, installed in BARC, India. During noise experiments, an Am-Be neutron source (1Ci) has been placed at the centre of the subcritical system. However, the proposed external neutron source in ADS, based on particle accelerator, is different from isotopic neutron source and the inherent fluctuations in beam current and accelerating voltage makes the source non-Poisson. In this context, Degweker and Rana had postulated a noise theory based on exponentially correlated Gaussian source characteristics for ADS. In noise experiments based on this postulate, a D-T neutron generator has been used in pulsed mode and source characterisation has been carried out to determine the distribution function, source correlation factor and D + beam pulse shape. It has been observed that the source is Gaussian in nature, the source correlation factor is very large compared to the prompt neutron decay constant and the pulsed D + beam is rectangular in shape. In noise experiments, the time stamped data have been analysed using various noise methods. The measured prompt neutron decay constant using Poisson source and correlated Gaussian source are in good agreement with theoretical value and amongst them.